Canonical PI3Kγ signaling in myeloid cells restricts Trypanosoma cruzi infection and dampens chagasic myocarditis - Maria C. Silva (Nature Portfolio, 2018)
Trypanosoma cruzi infection causes Chagas disease, but mechanisms underlying pathogenesis are unclear. Here, Silva et al. show that canonical PI3Kγ signaling in myeloid cells restricts T. cruzi infection in mice and that high PIK3CG expression correlates with low parasite levels in human Chagas’ hearts.